Agronomic performance of girl finger pepper under organic and mineral fertilization (Research, Society and Development, 2021)
The cultivation of peppers is carried out basically throughout the Brazilian territory, mainly by family farming. The use of alternatives to cheapen the production process, particularly in the use of inputs, is an alternative that can provide greater profitability for the farmer. Thus, the objective of this experiment was to evaluate the agronomic quality of the production of girl finger pepper under different doses of organic fertilizer and mineral fertilizer. The experimental design was in randomized blocks, with six treatments and four replications. The treatments were the doses of organic fertilizer: 0, 15, 30, 45 and 60 t ha-1 of bovine manure and a treatment with mineral fertilization. The agronomic performance of the crop was evaluated. The doses of organic fertilizer did not provide significant difference in productivity and in the number of fruits per pepper plant. The results were greater than in the control treatment. The doses of organic fertilizer of 45 and 60 t ha-1 provided higher yields of peppers than the control. The doses of organic and mineral fertilizer did not provide significant difference in the variables of production, length and diameter of fruits and pulp thickness. The highest index of agronomic efficiency in terms of productivity was obtained at a dose of 45 t ha-1 of organic fertilizer in relation to mineral fertilizer. The use of bovine manure can be indicated in the production of paprika pepper in the region of Ceres, GO.